Tensions in the performance of music: A symposium edited by Carola Grindea - Grindea, Carola; Nieman, Alfred; Lehrer, Paul; Howard, Leigh (London Kahn & Averill, 1995)
the contributors to this text are Grindea (piano), Havas (strings), Tausky (conducting), Nieman (composing), Gruner (voice), Howard (speech), Ben-Or (Alexander Technique), Lehrer (psychology), de Peyer (clarinet) and Jacobsen (tension control). The reprinted text also carries an additional chapter on guitar playing by Joseph O'Connor.